Pelatihan Membuat Ruang Belajar Metaverse Bagi Guru-Guru Di Wilayah Tangerang Selatan - Heni Jusuf; Magdalena, Maria; Istiyowati, Lucia Sri; Dazki, Erick; Santoso, Handri (Lembaga Penelitian Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2024)
After covid passed, many schools innovated in the learning process, so that the learning process could still run well. Students who have become accustomed to online learning need to be innovative again after COVID-19 has passed. The use of the metaverse has now been widely discussed for use in the learning process. Metaverse, a 3D digital space mixed with the real and virtual worlds, has been heralded as a future educational trend with great potential. However, as an emerging item, existing studies rarely discuss the metaverse from an educational perspective, so far, the metaverse is still used for games or product promotion. The community service that will be carried out is, so that teachers understand the concept of the metaverse, explain the role of the metaverse in the world of education and learning, design and build a simple metaverse ecosystem, operate metaverse applications, manage metaverse administration, choose pedagogic models that are suitable in the metaverse and represent the results of metaverse design. Thus, teachers are expected to make online learning fun. Training is held for ten (10) meetings, and each meeting is held for seven (7) hours. The results of the 100% training of participants consisting of 23 teachers ranging from kindergarten teachers to high school teachers, succeeded in creating a virtual learning space in the metaverse world.